PENEGAKAN HUKUM TERHADAP PEMBAKARAN SAMPAH SECARA ILEGAL (STUDY PEMBAKARAN SAMPAH DI KOTA SEMARANG) - Wisnu Heru Hartanto; Marius Yosep Sutedjo; Sabam Tua Paradongan; Diva Herdian Saputra; Arista Candra Irawati (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2026)
ABSTRACT Illegal waste burning in urban areas constitutes a practice that negatively impacts both the environment and public health. This study aims to analyze the legal basis, technical standards for waste management, law enforcement, and the effectiveness of enforcement against illegal waste burning in Indonesia, with a focus on Law No. 18 of 2008, Law No. 32 of 2009, and relevant regional regulations. The study employs a statutory and conceptual approach, integrating legal theories such as legal positivism, justice as fairness, substantive justice, legal realism, and economic analysis of law. The results indicate that the effectiveness of law enforcement is influenced by the capacity of law enforcement officers, inter-agency coordination, public participation, and the understanding and compliance with technical waste management standards. Public participation through mechanisms like Citizen Journalism has been shown to enhance monitoring and support enforcement. The study concludes that effective law enforcement requires an integration of formal legal norms, technical standards, competent enforcement officers, and active public participation to prevent illegal practices, protect environmental quality, and safeguard public health. This research contributes to the development of holistic environmental law theory and provides practical recommendations for government authorities, law enforcement agencies, academics, and the public in achieving sustainable waste management.